PENGEMBANGAN KERAJINAN SENI UKIR DAN BANGUNAN TRADISIONAL BALI DI DESA SINGAPADU TENGAH - I Wayan Parwata; I Nyoman Sutapa; Lilik Antarini; I Wayan Wesna Astara (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Central Singapadu Village is located in the Sukawati sub-district, Gianyar Regency, Bali. It is a traditional village that is still thick in customs and culture. Various economic activities that have developed since before the pandemic include: batik crafts, sculptures, carvings, paintings, Money Kepeng, handicrafts (handicrafts), and Balinese styl building crafts. The average resident in Central Singapadu village has the ability to craft Balinese-style buildings. Carving art is very influential on Balinese traditional buildings because in making Balinese traditional buildings various types of carvings are needed in it. In the midst of the dynamic development of micro, small, and medium enterprises, the community or business group is expected to have legality, while legacy ownership of its business is still low. The purpose of this activity is to see the development of community group businesses in Central Singapadu village, Gianyar which can be developed as regional superior products and increase community effort and creativity in an effort to improve their welfare. The method of implementing activities used is Asset Based on Community Development (ABCD) by emphasizing community business assets and mobilizing community assets into a pure opportunity for the community in encouraging businesses to become superior products. After this activity was carried out, the partners invited to collaborate in this activity experienced an increase in knowledge about anthropometric applications, the process of recording financial activities, carving techniques, and traditional Balinese buildings.